Argon indirect ophthalmoscopic photocoagulation: reduced potential phototoxicity with a fixed safety filter. Issue 4 (April 1990) - Whitacre, M M; Manoukian, N; Mainster, M A
Abstract : A new argon indirect ophthalmoscopic photocoagulator is presented which uses a red helium-neon laser aiming beam. An interference filter protects the operator from green or blue-green treatment beam reflections without impairing visualisation of the aiming beam or significant retinal anatomy. The protective filter is fixed in place, eliminating the weight, noise, and potential failure of mechanically switched filters. The red aiming beam has a negligible potential for producing photochemical retinal damage in the patient or operator.